Colorimetric detection of 2-tert-butyl-1, 4-benzoquinone in edible oils based on a chromogenic reaction with commercial chemicals. (30th January 2023) - Dong, Baolei; Qu, Hao; Yan, Ling; Liu, Changhong; Mao, Yu; Zheng, Lei
Highlights: Colorimetric strategy is established for rapid determination of TBBQ in edible oils. Specific chromogenic reaction between TBBQ and PEI is characterized. Rapid detection of TBBQ was achieved using commercial chemicals. Abstract: 2- tert -butyl-1, 4-benzoquinone (TBBQ) is the major oxidative product of tert -butylhydroquinone which is a widely used antioxidant in edible oils. The biotoxicity of TBBQ is a risk to human health, that the rapid and accurate monitoring of TBBQ is needed. Herein, a specific chromogenic reaction between TBBQ and polyethyleneimine (PEI) could generate adducts with maximum absorption at 478 nm. Amine groups of PEI are prone to link with TBBQ through Michael addition to form colored adducts. A colorimetric method for detecting TBBQ in edible oils was developed based on the aforesaid chromogenic reaction. The linear range for TBBQ was from 3.0 to 100.0 μg g −1, having a limit of detection of 1.8 μg g −1 . Recoveries results ranged from 88.4 % to 93.1 %, which had a good agreement with that of high-performance liquid chromatography. Our study provides a rapid and simple strategy for the sensitive detection of TBBQ using commercial chemicals.